State corporation: subject with special legal status - A N Kirsanov (RUDN Journal of Law, 2013)
This article deals with the legal status of State Corporation in comparison with the legal status of the JSC. The authors accent unique and specific characteristics of State Corporation, analyze its creation procedure and liquidation . They also evaluate advantages and disadvantages of this legal form of organization.